MANGROVE COMMUNITY STUDY MUNJANG CENTRAL BANGKA AS A MEANS OF PRESERVATION AND CONSERVATION EDUCATION LEARNING RESOURCES IN BANGKA BELITUNG - Sujadi Priyansah; Feni Kurnia (Edutainment : Jurnal Ilmu Pendidikan dan Kependidikan, 2025)
The purpose of this research is to analyze the study of the Munjang Mangrove community in Kurau Village as a learning resource for environmental conservation education in Bangka Belitung. This research design used a descriptive approach, using quantitative and qualitative methodologies through transect and plot methods. The research site was divided into five research stations. Each station consists of five transects, each transect measuring 100 meters in length, and each plot measuring 10 x 10 meters, with the measured parameters including species composition and diversity. Parameters measured include plant community composition and diversity. Parameters measured include the composition and diversity of mangrove species. The results showed the presence of 13 mangrove species, with the number of each plant found as follows: Calophyllum inophyllum, Bruguiera gymnorrhiza, Rhyzophora apiculata, Rhyzophora mucronata, Xylocarpus, Xylocarpus moluccensis, Excoecaria agallocha, Heritiera littoralis, Scaevola taccada, Morinda citrifolia, Avicennia alba, Pongamia pinnata, and Hibiscus tiliaceus. Xylocarpus mekogensis, Xylocarpus granatum, Rhyzophora apiculata, and Rhyzophora mucronata have high INP values, with each INP value exceeding 40%. This indicates that these species have an important role in the Kurau Village estuary. The mangrove diversity index in the Kurau Village Estuary is classified as moderate with a value of 2.1. The findings of the analysis of the relevance of research results in learning based on the 2013 curriculum show the existence of research links with biology learning, especially in biodiversity material for class X SMA with Basic Competency 3.2. Data analysis of observation results on various levels of biodiversity (genes, species, and ecosystems) in Indonesia is needed. The results of the identification of proposed efforts to preserve Indonesia's biodiversity were presented, and the results were based on the results of data analysis of threats to the preservation of various animal and plant diversity typical of Indonesia which were communicated in various forms such as herbarium.